A Neurological Outpatient Clinic for Patients With Post-COVID-19 Syndrome — A Report on the Clinical Presentations of the First 100 Patients - Boesl, Fabian; Audebert, Heinrich; Endres, Matthias; Prüss, Harald; Franke, Christiana (Frontiers in Neurology, 2021)
Neurological and psychiatric symptoms are frequent in patients with Post-COVID-19 Syndrome (PCS). Here, we report on the clinical presentation of the first 100 patients, who presented to our PCS Neurology outpatient clinic ≥12 weeks after the acute infection with SARS-CoV-2. To date, PCS is only defined by temporal connection to SARS-CoV-2 infection. Identification of clinical phenotypes and subgroups of PCS are urgently needed. We assessed clinical data of our first 100 ambulatory patients regarding clinical presentations, self-questionnaires focusing on daytime sleepiness, mood, fatigue and a screening assessment for detecting cognitive impairment. 89% of the patients presenting to the Neurology outpatient clinic had an initially mild course of COVID-19. The majority of the patients was female (67% versus 33% male). The most frequent symptom reported was cognitive impairment (72%). 30% of patients reporting cognitive deficits scored below 26 points on the Montreal Cognitive Assessment Scale (MoCA). Fatigue (67%), headache (36%) and persisting hyposmia (36%) were also frequently reported. 5.5% of all patients showed signs of severe depression. To our knowledge, this is the first report of patient data of a PCS Neurology outpatient clinic. Neurological sequelae also exist for more than 3 months after mainly mild SARS-CoV-2 acute infections. The reported symptoms are in accordance with recently published data of hospitalized patients.